2018
DOI: 10.1152/jn.00064.2018
|View full text |Cite
|
Sign up to set email alerts
|

Relative burst amplitude of muscle sympathetic nerve activity is an indicator of altered sympathetic outflow in chronic anxiety

Abstract: Relative burst amplitude of muscle sympathetic nerve activity (MSNA) is an indicator of augmented sympathetic outflow and contributes to greater vasoconstrictor responses. Evidence suggests anxiety-induced augmentation of relative MSNA burst amplitude in patients with panic disorder; thus we hypothesized that acute stress would result in augmented relative MSNA burst amplitude and vasoconstriction in individuals with chronic anxiety. Eighteen participants with chronic anxiety (ANX; 8 men, 10 women, 32 ± 2 yr) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 67 publications
(81 reference statements)
3
43
0
Order By: Relevance
“…Multiunit postganglionic MSNA was recorded from the peroneal nerve using standard microneurographic techniques as described in previous studies [35][36][37][38] and in the Online Data Supplement. Plasma norepinephrine concentration was assessed using high performance liquid chromatography.…”
Section: Sympathetic Nerve Activitymentioning
confidence: 99%
“…Multiunit postganglionic MSNA was recorded from the peroneal nerve using standard microneurographic techniques as described in previous studies [35][36][37][38] and in the Online Data Supplement. Plasma norepinephrine concentration was assessed using high performance liquid chromatography.…”
Section: Sympathetic Nerve Activitymentioning
confidence: 99%
“…Monocytes have been shown to be responsive to social isolation 29 and anxiety 28 . Social isolation and anxiety, produced by Western diet consumption, may be accompanied by increased sympathetic outflow and increased hypothalmic-pituitary adrenal production of cortisol, both of which modulate monocyte intracellular processes governing inflammatory molecule production [74][75][76] . Supporting the involvement of these systems, we previously reported that the Western diet group had increased sympathetic activity, and increased cortisol concentrations 77 .…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes have been shown to be responsive to social isolation (Cole, 2019) and anxiety (Cole et al, 2015). Social isolation and anxiety, produced by Western diet consumption, may be accompanied by increased sympathetic outflow and increased hypothalamic-pituitary adrenal production of cortisol, both of which modulate monocyte intracellular processes governing inflammatory molecule production (Cacioppo et al, 2015; Holwerda et al, 2018; Juruena et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…With larger sample sizes it may be possible to explore these mechanisms and also divide individuals into groups of positive, negative and nonresponders, that is, those with a mean change in MSNA burst frequency of <3 bursts/min during mental stress. Evidence suggests that anxiety disorders may be associated with augmented sympathetic activity during stress when compared with healthy controls (Park et al 2017;Holwerda et al 2018b). Park et al (2017) reported an overall increase in MSNA during mental stress, which was exaggerated in those with post-traumatic stress disorder (PTSD).…”
Section: Future Directionsmentioning
confidence: 99%